2021
DOI: 10.1093/ibd/izab147
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Pediatric MRI-Based Perianal Crohn Disease (PEMPAC) Index—A Report from the ImageKids Study

Abstract: Background As part of the prospective multicenter ImageKids study, we aimed to develop and validate the pediatric MRI-based perianal Crohn disease (PEMPAC) index. Methods Children with Crohn disease with any clinical perianal findings underwent pelvic magnetic resonance imaging at 21 sites globally. The site radiologist and 2 central radiologists provided a radiologist global assessment (RGA) on a 100 mm visual analog scale a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Given that MAGNIFI-CD [15] and PEMPAC [16] were developed through a combination of expert opinion and assessment of disease severity on a 100 mm visual analog scale, the strong association between the CD-PAF MR scoring systems and radiologists' subjective severity assessments is consistent with their design. However, the magnitude of change in these scores that would constitute radiological healing remains undefined without a direct correlation between pathology and imaging findings.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Given that MAGNIFI-CD [15] and PEMPAC [16] were developed through a combination of expert opinion and assessment of disease severity on a 100 mm visual analog scale, the strong association between the CD-PAF MR scoring systems and radiologists' subjective severity assessments is consistent with their design. However, the magnitude of change in these scores that would constitute radiological healing remains undefined without a direct correlation between pathology and imaging findings.…”
Section: Discussionmentioning
confidence: 87%
“…This study evaluated the radiologist performance characteristics of CD-PAF MR scoring systems, including MAGNIFI-CD [15], mVAI [14], and PEMPAC [16], in a real-world cohort of patients with CD-PAF who underwent serial imaging with pelvic MR. In our study design, the MR scoring systems are responsive in assessing changes in disease severity and show associations with radiologists’ subjective impressions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the fistula length was significantly shorter in patients who did not form perianal abscess ( p = 0.006). A study by Choshen et al highlighted that the best imaging findings indicating the severity of pediatric perianal CD were presence of collections >3 mm, location and length of the fistulas ( 27 ). Also, a previous study on MRI predictors of treatment response in children with CPF reported that maximum fistula length ≥2.5 cm was a predictor of disease progression ( 15 ).…”
Section: Discussionmentioning
confidence: 99%